Prenatal yoga for physical and psychological health during women’s pregnancy: a scoping review - Migita Vidia Amita; Elsye Maria Rosa; Anjarwati Anjarwati; Cesa Septiana Pratiwi (Universitas 'Aisyiyah Yogyakarta, 2022)
Throughout pregnancy, women’s pregnancy will undergo physical and psychological changes. Prenatal yoga can train pregnant women physically, psychologically and spiritually for pregnancy and preparation for childbirth. For reviewing the evidence related to the impacts of prenatal yoga on the physical and psychological features of women’s pregnancy. The arrangement of scoping review adopted using Scoping Review PRISMA-ScR. The inclusion criteria for choosing relevant articles were based on original articles published between 2010 until 2020 from database sources namely Wiley Online Library, PubMed, and EBSCO, and free access articles available in full-text format. Form 2,548 data selection using PRISMA ScR have obtained 14 articles which fulfilled the inclusion criteria and for critical appraisal using the Joanna Riggs Institute tools. Based on 14 articles obtained, nine articles used the randomized controlled trial method, four used the quasi-experiment method, and one used the qualitative focus group discussion method. The result showed two themes: (1) the physical advantages of gentle prenatal yoga for women’s pregnancy were strengthening immunity (Ig A), decreasing the intensity of back pain, and reducing the intensity of leg pain, and (2) the psychological advantages of gentle prenatal yoga for women’s pregnancy as a stress intervention experienced, as an intervention to decrease depression symptoms experienced, discomfort reduction due to sleep disorder, intervention anxiety intervention experienced, decreasing cortisol level, decreasing saliva a-amilase, and enhancing mood. The research finding showed that prenatal yoga is beneficial for women’s pregnancy physically and psychologically as an intervention to the changes those women’s pregnancy during pregnancy.